A COMPARATIVE ANALYSIS OF PUBLIC SECTOR ACCOUNTABILITY - Neilson, John; Tower, Greg (The journal of contemporary issues in business and government, 2007)
This paper provides a comparative analysis of change in the accountability regime - from a fiduciary focus to a more relative and useful managerial accountability focus - across Australian local government. Six Australian states are reviewed revealing important differences between local government accountability across jurisdictions. Differences are evidenced in the demographic factors including financial capabilities, age and size of local governments. This study provides an important contribution to our understanding of public sector accountability in local government by documenting the increased emphasis in managerial decision making.